CE (Cost Effective) Crab House - Saiful Bahari, Mohd Yusoff; Zalina, Ibrahim; Samsur, Mohamad (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
At present, Mud Crab demand is high and Sarawak being blessed with many rivers and potentially fulfil the demand of mud crab locally. The mud crab that is from Santubong and Sematan are known to be in one of the top quality produce. In Sarawak, there are some locals who deal with mud crab farming and most of them doing a conventional mud crab farming such as pond farming. Hence, the CE-Crab House is innovated to help the lower income community to generate their income. The CE-Crab House is a cost effective crab fattening house that is newly improved design for the purpose of high volume production. The CE-Crab House is able to fatten mud crabs using a DIY design, low cost with a systematic monitoring process.